UPAYA PENINGKATAN HASIL PEMBELAJARAN GERAK DASAR GULING DEPAN DENGAN METODE BERMAIN KELAS II SD NEGERI 028 RIMBO PANJANG KECAMATAN TAMBANG KABUPATEN KAMPAR TAHUN 2021 - Tarwiyah (EduTeach : Jurnal Edukasi dan Teknologi Pembelajaran, 2022)
This research is motivated by the ineffectiveness of learning methods to improve students' movement skills. This study aims to determine the increase in learning outcomes for the front roll basic motion with the second grade playing method at SDN 028 Rimbo Panjang, Tambang District, Kampar Regency.This research is a classroom action research (classroom action research) which is carried out in a collaborative and participatory manner. This research design uses Kurt Lewin's model in 1 cycle consisting of planning, implementation & observation, and reflection. The research subjects included second grade students at SDN 028 Rimbo Panjang with 35 students consisting of 19 male students and 16 female students. The object of the research is to increase the effectiveness of learning the front roll with the play method. Data collection techniques through performance tests. The data analysis technique was carried out descriptively, qualitatively and quantitatively.The results showed that the effectiveness of learning the basic forward roll with the playing method for class II SDN 028 Rimbo Panjang, Tambang District, Kampar Regency which had been obtained by students, overall there were 28 students or 80% completed learning and 7 students or 20% had not finished learning. This research has achieved research success indicators, namely 80% of students have minimum learning mastery in the complete learning category with a Minimum Mastery Criteria of 80, so there is no need for further action in the next cycle.